The last great road bum - Tobar, Héctor, 1963- (MCD, Farrar, Straus and Giroux, 2020)
"In The Last Great Road Bum, Héctor Tobar turns the peripatetic true story of a naive son of Urbana, Illinois, who died fighting with guerrillas in El Salvador into the great American novel for our times. Joe Sanderson died in pursuit of a life worth writing about. He was, in his words, a 'road bum,' an adventurer and a storyteller, belonging to no place, people, or set of ideas. He was born into a childhood of middle-class contentment in Urbana, Illinois and died fighting with guerillas in Central America. With these facts, acclaimed novelist and journalist Héctor Tobar set out to write what would become The Last Great Road Bum. A decade ago, Tobar came into possession of the personal writings of the late Joe Sanderson, which chart Sanderson's freewheeling course across the known world, from Illinois to Jamaica, to Vietnam, to Nigeria, to El Salvador - a life determinedly an adventure, ending in unlikely, anonymous heroism. The Last Great Road Bum is the great American novel Joe Sanderson never could have written, but did truly live - a fascinating, timely hybrid of fiction and nonfiction that only a master of both like Héctor Tobar could pull off."--Provided by publisher.